Digital Branding Training for MSMEs to Increase Competitiveness of Beringharjo Market Traders - Arridho Ramadhan Firdaus; Syafika Dhea Taqiya Ramadhani; Tri Suwarno; Wildan Muhammad Ardana; Ula Restu Rafifah (Universitas AMIKOM Yogyakarta, 2026)
East Beringharjo Market faces a major challenge in maintaining competitiveness due to low digital literacy and the lack of a strong brand identity among traders. This community service activity aims to improve digital branding literacy and equip traders with technical skills in managing business social media. The implementation method involves five stages: preparation, visual branding training, digital marketing training, implementation mentoring, and evaluation. Participants in this activity consisted of a team of lecturers and students from Universitas ‘Aisyiyah Yogyakarta and traders who are members of the East Beringharjo Market Traders Association. The results of the activity showed a significant increase in participants' understanding, where the average evaluation score increased from 35.00 in the pre-test to 84.29 in the post-test. The empirical impact of this activity is the formation of visual identities in the form of logos and active business accounts managed professionally by the traders. In conclusion, intensive mentoring can accelerate digital transformation and increase the economic independence of traditional market traders in the digital era.